Strategi Mengoptimalkan Manajemen Kinerja Karyawan Melalui Konsep Organizational Citizenship Behavior (OCB): Suatu Kajian Literatur - Edi Irawan (Jurnal Publikasi Ilmu Manajemen, 2023)
This article aims to review and attempt to confirm the strategy for optimizing employee performance management through the concept of organizational citizenship behavior ( OCB). The research method used is qualitative and literature studies or library research. Based on the results and discussion, it can be concluded that to optimize employee performance management through organizational citizenship behavior ( OCB) it can be done with three factors, namely spiritual intelligence, leadership  style and organizational culture. The position of spiritual intelligence in shaping organizational citizenship behavior ( OCB)  and employee performance is very important because spiritual intelligence contains several aspects that are characteristic of high spiritual intelligence, namely: friendly attitude, closeness, curiosity, creativity, construction, self mastery and religion. Likewise, the element of leadership style is also an important element in employee performance management because leadership is a process by which an individual influences other members of the organization to work together to achieve organizational goals. As well as the elements of organizational culture in their influence on optimizing employee performance management is very strong, because in a strong culture, the main values of an organization or company are highly upheld and especially for all employees, the more employees who accept these values and the greater the commitment to them, the stronger the corporate culture. This strong culture will form cohesiveness, loyalty and commitment to the company in its employees which will reduce the desire of employees to leave the organization or company.